Comparison Between Collaborative Group Learning and Individual Learning in Improving English Reading Skill at SMA Negeri 1 Seputih Banyak - RISMA LUTHFIA SAFIRA SAFIRA; Ag. Bambang Setiyadi; Rafista Deviyanti (English Language Education Study Program, 2026)
This study compared collaborative group learning and individual learning to determine which produced greater improvement in students' English reading skills at SMA Negeri 1 Seputih Banyak. A quasi-experimental pre-test and post-test design was used. Two classes of eleventh-grade students were selected through random sampling in the 2025/2026 academic year, resulting in 66 participants: an experimental group (n = 30) receiving collaborative group learning and a control group (n = 36) receiving individual learning, both using analytical exposition texts over three meetings. Reading comprehension was measured across five aspects: main idea, supporting details, vocabulary, inference, and text structure, analyzed via paired samples and independent samples t-tests in SPSS. Both methods produced statistically significant improvement (p = .000). The independent samples t-test revealed a significant difference between groups (t = 3.270, p = .002), with the individual learning group achieving a higher post-test mean (78.61) than the collaborative group learning group (74.60), confirming individual learning as the superior method in this context. Supporting details showed the highest numerical gain in both groups, while inference demonstrated the greatest proportional improvement (79.5% in the control group; 75% in the experimental group). Individual learning outperformed collaborative group learning across all five reading aspects, likely because the naturally teacher-centered classroom environment meant students were already accustomed to independent study.